The Rule of Law and the Extraordinary Situation - Karácsony, András; Nagypál, Szabolcs (Public Governance, Administration and Finances Law Review, 2021)
The various legal theorists dealing with the operation and effect of law have mostly examined situations that can be described as occurring in the usual, regular, normal state of social life. Over the last half century, and particularly since the formation and later enlargement of the European Union, the requirement of the rule of law has emerged as a key topic. The test of the rule of law is as follows: it is necessary to examine in an abnormal situation or, as it were, in an extraordinary situation exactly how it is possible to take political decisions that are of fundamental importance to society while also guaranteeing that these decisions remain within the rule of law at all times. The aim of this study is to investigate how and by what constitutional mandate the Hungarian Government deviated from the normal constitutional situation in 2020. The “state of exception” theorised by Carl Schmitt and Giorgio Agamben means the suspension of the law. It is important to understand their views in order to see that the Hungarian situation in 2020 is utterly dissimilar to such a state of exception. In short, we need to distinguish a state of exception from an extraordinary situation, because the latter does not imply the suspension of law in general or, more specifically, the suspension of the rule of law, but that parliamentary and government decisions remain within it. The special legal order applied in an extraordinary situation is not in fact a suspension of democracy, still less of the rule of law. On the contrary, it actually falls within both: in a state of national crisis, this situation is democracy itself and the rule of law itself, and – accordingly – strict laws (both democratic and imposed within the rule of law), or rather laws of cardinal importance, make its conditions and its functioning possible and regulate it.